2022
DOI: 10.15252/embj.2022112107
|View full text |Cite
|
Sign up to set email alerts
|

Human SFI1 and Centrin form a complex critical for centriole architecture and ciliogenesis

Abstract: Over the course of evolution, the centrosome function has been conserved in most eukaryotes, but its core architecture has evolved differently in some clades, with the presence of centrioles in humans and a spindle pole body (SPB) in yeast. Similarly, the composition of these two core elements has diverged, with the exception of Centrin and SFI1, which form a complex in yeast to initiate SPB duplication. However, it remains unclear whether this complex exists at centrioles and whether its function has been con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 66 publications
3
24
0
Order By: Relevance
“…As previously described, POC5 depletion did not alter percentage of cells with distal SFI1 centriolar pools (Fig. 6D, E) (Laporte et al, 2022). These results identify CCDC15 as a dual regulator of centriolar recruitment of inner scaffold protein POC1B and the distal end SFI1/Centrin complex.…”
Section: Ccdc15 Regulates Centriole Length and Structuresupporting
confidence: 88%
See 3 more Smart Citations
“…As previously described, POC5 depletion did not alter percentage of cells with distal SFI1 centriolar pools (Fig. 6D, E) (Laporte et al, 2022). These results identify CCDC15 as a dual regulator of centriolar recruitment of inner scaffold protein POC1B and the distal end SFI1/Centrin complex.…”
Section: Ccdc15 Regulates Centriole Length and Structuresupporting
confidence: 88%
“…Previous studies showed that the inner scaffold proteins including WDR90, Centrin-2 and POC5, as well as the distal SFI1/Centrin complex are required for proper cilium formation and function (Delaval et al, 2011; Hassan et al, 2019; Laporte et al, 2022; Prosser and Morrison, 2015; Steib et al, 2020). To investigate whether CCDC15 functions in cilium assembly, we depleted CCDC15 in RPE1 cells and quantified the percentage of ciliated cells upon 48-h serum starvation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been found to be related to inflammatory bowel disease ( 18 ), X-linked myotubular myopathy ( 17 , 19 ), and type 4B Charcot-Marie-Tooth disease ( 20 ). SFI1 (SFI1 Centrin Binding Protein), essential for proper stability of centrioles and ciliogenesis regulation ( 21 ), is associated with diabetic nephropathy ( 22 ), neuroblastoma ( 23 ), and microcephaly ( 24 ). However, MTMR3:: SFI1 fusion has not been previously reported.…”
Section: Discussionmentioning
confidence: 99%